Efficacy of Different Coloured Sticky Traps Against Thrips of Chilli - Hossain, M.M.; Khalequzzaman, K.M.; Alam, M.S.; Mondal, M.T.R.; Islam, M.M. (International Journal of Applied Sciences and Biotechnology, 2020)
The field experiment was conducted at Spices Research Centre, Shibganj, Bogura, Bangladesh during Rabi season of 2017-18 to study the color preference of Scirtothrips dorsalis in chilli. The treatments were T1= Blue trap @40 trap/ha; T2= Yellow trap @40 trap/ha; T3= White trap @40 trap/ha; T4= Green trap @40 trap/ha and T5= Pink trap @40 trap/ha. Among the color traps used, at 35 days after installation (DAI) of trap blue color attracted highest (8.44 thrips/ sq. inch area of trap) number of S. dorsalis adults followed by white (5.43 thrips/ sq. inch area of trap), yellow (4.30 thrips/ sq. inch area of trap), green (3.52 thrips/ sq. inch area of trap) and pink (3.40 thrips/ sq. inch area of trap) color. Blue coloured sticky trap also attracted comparatively a smaller number of beneficial insects and can be used for relative estimate of S. dorsalis population and also for monitoring and mass trapping as a component of IPM program. Int. J. Appl. Sci. Biotechnol. Vol 8(2): 187-190